ANALISIS PENGARUH BEBAN KERJA, MANAJERIAL DAN LINGKUNGAN KERJA TERHADAP KINERJA PENDIDIK DI SEKOLAH DASAR KATOLIK SANTA MARIA - Risdayanti; Camelia Leisubun; Abu Bakar (CV. Adiba Aisha Amira, 2026)
This study aims to analyse the influence of workload, managerial factors and the working environment on the performance of teachers at Santa Maria Catholic Primary School in Timika. The research method employed is an associative method using a quantitative approach. The research population comprised all teaching staff at Santa Maria Catholic Primary School, and the sampling technique employed a census method. Data were collected via questionnaires, observations, and documentation, and subsequently analysed using multiple linear regression with the aid of SPSS to test the influence of each variable both simultaneously and partially. The results of the study indicate that workload has a positive and significant influence on teachers’ performance. Meanwhile, the headteacher’s managerial style has a positive and significant effect on teachers’ performance, and the work environment has a positive and significant effect on teachers’ performance. Simultaneously, these three independent variables make a significant contribution to improving teachers’ performance.